Distance of neuromuscular attack and response in high competition wrestlers - Omar Iglesias-Pérez; Zelma Quetglas-González; Julio Mendieta-Cuellar (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
In the last years the wrestlers and Cuban trainers have reached remarkable results in wrestling; at world level important individual victories have been conquered in the Olympic Games, world and regional championships, as well as for teams in world cups and regional games. The outstanding results of our sportsmen are due to the creative and collective work of the trainers, scientific, specialists and the own athletes fundamentally. One of the main problems detected in world championships, world cups and Olympic games, is the insufficient distance of the free style wrestlers; if it were determined each athlete effective distance, this problem could be eliminated, and this way to better personalize the athlete. For such a reason in this work it is hoped to elaborate a biomechanical model to determine the ideal distance attack, considering each athlete's individual anthropometrical characteristics and his explosive strength; response time of each athlete, mainly the time of latency and the time of reaction.